SUDDEN DEATH DUE TO RESPIRATORY TRACT DISEASES - Abdul Gafar Parinduri (Universitas Muhammadiyah Sumatera Utara, 2019)
Sudden death is death that occured within 24 hours since of the onset symptoms. Forensic cases, most occur within minutes or even the first seconds of appearance. Sudden death causes can be applied according to the body system, there are central nervous, respiratory, gastrointestinal, haemopoietic, and the endocrine system. Sudden death from respiratory illness is one of the causes of sudden and natural deaths worldwide. Incidence of sudden death in developing countries has a higher frequency. One of the respiratory ailments that causes sudden death is tuberculosis. Case report:a 35 year-old female has been carried out outside examination and in (autopsy) on the corpse. Autopsy was found that lung attachment with chest cavity. Right and left lung was full of foam mixed with pus. This verification supports that the cause of sudden death was due to chonic lung disease.Keywords: Corpse autopsy, pulmonary tuberculosis, sudden death, respiratory disease